Real-world data of long-term survival in patients with T-cell lymphoma who underwent stem cell transplantation - Dong Won Baek; Joon Ho Moon; Jae Hoon Lee; Ka-Won Kang; Ho Sup Lee; Hyeon-Seok Eom; Enuyoung Lee; Ji Hyun Lee; Jeong-Ok Lee; Seong Kyu Park; Seok Jin Kim; Keon Hee Yoo; et al. (Blood Cancer Journal, 2023)
Abstract This study aimed to identify the benefits of autologous-stem cell transplantation (auto-SCT) and allogeneic-SCT (allo-SCT) in patients with aggressive T-cell lymphomas to aid in the selection of transplantation type in clinical practice. This study retrospectively analyzed data from 598 patients who underwent transplantation for T-cell lymphomas from 2010 to 2020. In total, 317 patients underwent up-front SCT as consolidation therapy. The 3-year progression-free survival (PFS) and overall survival (OS) were 68.7% and 76.1%, respectively. Patients who underwent auto-SCT had significantly better OS (p = 0.026) than those who underwent allo-SCT; however, no statistical difference in PFS was found. Transplantation was used as a salvage therapy in 188 patients who had relapsed/refractory disease. Overall, 96 (51.1%) patients underwent auto-SCT and 92 (48.9%) patients underwent allo-SCT. Auto-SCT improved long-term survival in patients with complete remission (CR). Allo-SCT demonstrated better 3-year PFS in patients with partial remission and relapsed/refractory disease status. However, >50% of patients died within 1 year of allo-SCT. As a consolidative therapy, up-front auto-SCT demonstrated a survival benefit. Auto-SCT was also effective in patients who achieved CR after salvage therapy. If the disease persists or cannot be controlled, allo-SCT may be considered with reduced intensity conditioning.